A study on the (π- , K+) reaction production of Σ-hypernuclei - Petridou, Theodora (HNPS Advances in Nuclear Physics, 2019)
The ( π - , K+) reaction production was used recently to produce medium to heavy Σ-hypernuclei with good statistics. The observed spectra do not contain peaks and have a wide energy range. These spectra were studied within the Green function method with a simplified model. The investigation showed that a strong repulsive potential with medium imaginary and spin-orbit parts describes well the spectra.